A method for accurately separating multi-layer copper foil, multi-layer copper foil and printed circuit board thereof
By analyzing the ratio of the radius of the ellipsoid copper tumor on the surface of the copper foil, the separation force of the carrier copper foil is accurately adjusted, and the problem of difficult to accurately control the separation force in the prior art is solved, and a stable separation effect is achieved without affecting other performances.
Patent Information
- Application Number
- CN202411812045.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to precisely control when adjusting the separation force of the carrier copper foil, and the adjustment process may affect other performance parameters such as durability and adhesion.
By analyzing the ratio of the vertical copper tumor radius (a) and the horizontal copper tumor radius (b), the separation force is accurately analyzed and adjusted, and the precise separation of multi-layer copper foil is achieved.
Accurate control of the separation force of copper foil is achieved, ensuring that the separation force is stable within different ranges and does not affect other performance parameters, reducing production costs and shortening production cycles.
Smart Images

Figure HDA0005180777220000011 
Figure HDA0005180777220000012 
Figure HDA0005180777220000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of copper foil processing, and in particular to a method for accurately separating multiple layers of copper foil, multiple layers of copper foil and a printed circuit board thereof. Background Art
[0002] With the rapid development of information technology, consumer electronic products have a trend of becoming lighter, thinner and smaller. As a packaging substrate material connecting chips and PCB circuit boards, it is constantly breaking through to multi-layer and thinner. As one of the key raw materials in packaging substrates, the thickness of copper foil is the key to the breakthrough of packaging substrates to multi-layer and thin. Although the thickness of conventional copper foil products can reach 6μm, it pales in comparison to nano-process chips. In order to produce thinner copper foil, the industry has developed carrier copper foil technology, which solves the problem of extremely thin copper foil being difficult to mass produce by attaching copper foil with a thickness of ≤3μm to a copper foil carrier with a thickness of ≥9μm.
[0003] Carrier copper foil is usually composed of two layers of copper foil, one of which is a carrier copper layer as a support, and the other is an extremely thin copper layer as the main body. During the use of this material, the two layers of copper foil need to be separated for further processing and assembly. Among them, due to the separation process between the two layers of copper foil, a certain force needs to be applied to separate them, and this force is called separation force.
[0004] The separation process of the carrier copper foil is realized by the peeling layer between the two layers of copper foil. The peeling solution of the prior art is to use other metals or organic coatings between the two layers of copper foil to achieve it. Since the carrier copper foil needs to be pressed with the prepreg at high temperature during subsequent use, and the carrier copper layer will be separated and removed after pressing, leaving only the copper clad laminate with the prepreg and the extremely thin copper layer. Therefore, the peeling layer needs to have a certain temperature resistance so that the copper foil can still maintain the separable performance after being pressed with the plate in subsequent use.
[0005] The existing technology mainly adjusts the separation force of the carrier copper foil by adjusting the content of inorganic or organic components in the peeling layer. The principle of this method is to change the bonding force between the two layers of copper foil and the peeling layer by changing the chemical properties of the peeling layer, thereby achieving control of the separation force. However, the existing technology has some problems in adjusting the separation force of the carrier copper foil. First, since the content of inorganic or organic components in the peeling layer is a quantitative value, the slight difference in the content of the substance in the peeling layer will affect the value of the separation force, and it is difficult to accurately control its composition only by the electroplating or coating process during the electroplating process. Therefore, the separation force adjusted by this method is also quantitative and difficult to accurately control. In this context, if certain applications require higher or lower separation forces during use, the existing technology may be difficult to meet actual needs. Secondly, adjusting the content of inorganic or organic components in the peeling layer may affect other performance parameters, such as the durability and adhesion of the peeling layer, thereby affecting the overall performance of the copper foil. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for accurately separating multi-layer copper foils, by analyzing the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b), the separation force is accurately analyzed to achieve accurate separation of multi-layer copper foils; wherein,
[0007] When the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) is 0.8<a / b≤1.6, after the two layers of copper foil are pressed at a temperature above 210°C, the separation force of the two layers of copper foil is between 5≤F<20gf / cm;
[0008] When the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) is 0.5<a / b≤0.8, after the two layers of copper foil are pressed at a temperature above 210°C, the separation force of the two layers of copper foil is between 20≤F<50gf / cm;
[0009] When the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) is 0.3<a / b≤0.5, after the two layers of copper foil are pressed at a temperature above 210°C, the separation force of the two layers of copper foil is between 50≤F<80gf / cm.
[0010] A second aspect of the present invention provides a multi-layer separable copper foil, which is precisely separated by using the method described above.
[0011] As an embodiment of the present invention, the cross-sectional structure of the copper foil is respectively a carrier copper layer, a separation force adjustment layer, an isolation coating layer, an ultra-thin copper layer, and a surface treatment layer from bottom to top.
[0012] As an embodiment of the present invention, the surface roughness Rz of the carrier copper layer in contact with the ultra-thin copper layer is between 0.5≤x<3.0μm, Sdr is between 1.5≤y<20.0%, and the peak density Spd is between 5000≤y<30000 (1 / mm 2 )
[0013] As an embodiment of the present invention, the isolation coating is selected from one of an electrodeposited non-copper metal, an organic coating, and a mixed coating of an electrodeposited non-copper metal and an organic coating.
[0014] The third aspect of the present invention provides a method for preparing the multi-layer separable copper foil, the steps of which are as follows:
[0015] (1) Electrolytic equipment to prepare the first copper layer:
[0016] The electrolyte is a copper sulfate solution containing 110 g / L sulfuric acid and Cu 2+ CuSO4·5H2O with an ion concentration of 97g / L; in an electrolyte with a temperature of 54°C and a current of 36A / dm 2 Electrolysis was performed for 50 seconds at a current density of 1.50 μm to obtain a first copper foil with a thickness of 18 μm.
[0017] (2) Surface roughness treatment:
[0018] After the first copper layer is prepared, sulfuric acid and Cu2O3 at a concentration of 80 g / L are used on its surface. 2+ The surface roughness was adjusted by using a CuSO4·5H2O electrodeposition solution with an ion concentration of 30 g / L, and ellipsoidal copper particles were generated on the surface; the electrodeposition temperature was 40°C and the current density was 25 A / dm 2 , electrolysis time is 7s;
[0019] After the roughened surface is prepared, sulfuric acid is used as a treatment liquid to spray and soak both sides of the copper foil for 20 seconds to remove surface impurities or oxide film; the treatment liquid is sulfuric acid with a concentration of 85g / L and a treatment liquid temperature of 40°C;
[0020] (3) Preparation of isolation coating
[0021] After removing impurities or oxide film on the surface of the copper foil, the copper foil is brought into an isolation coating electrolyte to prepare an isolation coating; the concentration of gritty anhydride in the adhesion layer metal electrolyte is 0.5 g / L, the concentration of potassium pyrophosphate is 700 mg / L, and the electrolyte temperature is 45°C; after 12 seconds of electroplating, the surface metal liquid is removed by an immersion rinse tank, and brought into an organic attachment liquid for physical adsorption, the organic attachment liquid is a 3 g / L benzotriazole aqueous solution, the attachment liquid temperature is 35°C, and the immersion attachment time is 20 seconds; and then the isolation coating is obtained after air drying in a blast oven at 150°C;
[0022] (4) Preparation of ultra-thin copper layer
[0023] After the first layer of isolation coating is air-dried, the copper foil is placed in a solution containing 110 g / L sulfuric acid and Cu 2+ CuSO4·5H2O with an ion concentration of 97g / L; in an electrolyte with a temperature of 54°C and a current of 20A / dm 2 Electrolysis was performed for 8 seconds at a current density of , and an extremely thin copper layer with a thickness of 3.0 μm was obtained;
[0024] (5) Roughening treatment
[0025] The copper foil obtained in step (4) is introduced into a sulfuric acid solution having a concentration of 90 g / L and Cu 2+ In the copper sulfate solution electrolyte with an ion concentration of 25g / L, the second copper layer is opposite to the anode plate, and the first copper layer is far away from the anode plate. 2 The copper foil was electroplated at an average current density of 95 g / L and Cu 2+ Solidification electroplating was carried out in a copper sulfate solution with an ion concentration of 55g / L and an electroplating current density of 15A / dm 2 , electroplating time 15s;
[0026] (7) Surface treatment layer
[0027] The structure obtained in step (5) is first electrolyzed in an electrolyte with a sulfuric acid concentration of 75 g / L, a cobalt concentration of 10 g / L, a boric acid concentration of 30 g / L, and a sodium citrate concentration of 10 g / L at a temperature of 40°C and a current density of 12 A / dm 2 , electroplating time 10s; then at sulfuric acid concentration 85g / , zinc concentration 18g / L, chloride ion concentration 15ppm, boric acid 30g / L, sodium citrate 15g / L, electrolysis temperature 45℃, current density 10A / dm 2 , the electroplating time is 10s; finally, the electrolyte or water stains on the surface are removed by spraying water washing and oven drying.
[0028] The third aspect of the present invention provides a printed circuit board prepared from the multi-layer separable copper foil.
[0029] By adopting the above technical solution, the present invention has the following beneficial effects:
[0030] 1. Precisely control the separation force: The present invention effectively adjusts the separation force by physical means by adjusting the ratio of the radius of the ellipsoidal copper nodule on the contact surface between the carrier copper layer and the ultra-thin copper layer. The separation controllable of the present invention is specifically that when the ratio of the vertical copper nodule radius (a) of the separation force adjustment layer to the horizontal copper nodule radius (b) is 0.8<a / b≤1.6, after the copper foil is subjected to a pressing temperature of more than 210°C, the separation force of the two layers of copper foil is between 5≤F<20gf / cm; when the ratio of the vertical copper nodule radius (a) of the separation force adjustment layer to the horizontal copper nodule radius (b) is 0.5<a / b≤0.8, after the copper foil is subjected to a pressing temperature of more than 210°C, the separation force of the two layers of copper foil is between 20≤F<50gf / cm; when the ratio of the vertical copper nodule radius (a) of the separation force adjustment layer to the horizontal copper nodule radius (b) is 0.3<a / b≤0.5, after the copper foil is subjected to a pressing temperature of more than 210°C, the separation force of the two layers of copper foil is between 50≤F<80gf / cm;
[0031] 2. The stability of the separation force is guaranteed, and the separation force test range is less than 8, which is beneficial for copper foil manufacturers to prepare carrier copper foil products with a wider width.
[0032] 3. No influence on other performance parameters: The adjustment method of the present invention is through physical means, rather than by changing the content of inorganic or organic components in the peeling layer. Therefore, the adjustment of the present invention will not affect other performance parameters such as durability and peeling strength of the peeling layer, thereby ensuring the performance of the overall material.
[0033] 4. Reduce production costs and shorten production cycles: The adjustment method of the present invention does not require complex chemical treatment of the peeling layer, but only requires adjusting the roughness. This not only reduces production costs, but also shortens the production cycle, which is conducive to large-scale production.
[0034] 5. Providing a new adjustment idea: The adjustment method of the present invention provides a new idea for adjusting the separation force of the carrier copper foil, which has a potential driving effect on the technical development of related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 Schematic diagram of the copper foil structure provided in Example 1 of the present invention; wherein: 1-carrier copper layer; 2-separation force adjustment layer; 3-isolation layer; 4-ultra-thin copper layer; 5-surface treatment layer;
[0037] Figure 2 For the separation force adjustment layer morphology comparison Figure 2 -a is Example 1; Figure 2 -b is comparative example 1.
[0038] Figure 3 The separation force test diagram is shown in Figure 3-a, which is Example 1; Figure 3 -b is comparative example 1.
[0039] Figure 4 Schematic diagram of the separation force adjustment layer, where 2-1-separation force adjustment layer copper nodule; 3-isolation layer; 4-ultra-thin copper layer; a-vertical copper nodule radius; b-horizontal copper nodule radius.
[0040] Figure 5 This is an electron microscope image of the contact surface between the ultra-thin copper layer and the separation force adjustment layer after peeling off. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The present invention mainly adopts the following technical means: by accurately controlling the ratio of the radius of the ellipsoid copper nodules, quantitative adjustment of the separation force is achieved. High-precision measuring equipment, such as a fine copper foil stripping machine, is used to accurately measure the roughness of the surface of the carrier copper layer, thereby achieving precise adjustment of the separation force. In order to avoid the influence of this scheme on other performance parameters, this scheme only adjusts the interlayer roughness and will not affect other performance parameters, such as the durability and adhesion of the stripping layer, thereby ensuring other physical properties of the carrier copper foil.
[0043] The problem of quantitative adjustment of separation force: the existing technology adjusts the separation force of the carrier copper foil by adjusting the content of inorganic or organic components in the peeling layer, but the adjustment range of this method is quantitative and difficult to control accurately. The present technical solution adjusts the separation force effectively by physical methods by adjusting the ratio of the radius of the ellipsoidal copper nodule on the contact surface of the carrier copper layer with the ultra-thin copper layer, thereby achieving quantitative adjustment of the separation force. The stability of the separation force is improved. The separation force of the copper foil of the present invention has a greater influence on the regulation of force in the physical direction than the chemical one due to the participation of mechanical force, so the test range of its separation force is <8; the problem of influence on other performance parameters: the existing technology may affect other performance parameters when adjusting the separation force of the carrier copper foil, such as the durability and adhesion of the peeling layer, thereby affecting the performance of the overall material. The present technical solution only adjusts the separation force by adjusting the roughness, which will not affect other performance parameters, thereby ensuring that the performance of the overall material remains unchanged.
[0044] The present invention is further explained below in conjunction with specific implementation modes.
[0045] Example 1
[0046] This embodiment provides a multi-layer separable copper foil, which comprises a carrier copper layer, an isolation coating layer, an ultra-thin copper layer, and a roughening layer from bottom to top. The preparation method of the multi-layer separable copper foil is as follows:
[0047] (1) The first copper layer is prepared by electrolysis equipment. The electrolyte is a copper sulfate solution containing sulfuric acid with a concentration of 110 g / L and Cu 2+ CuSO4·5H2O with ion concentration of β97g / L. In an electrolyte with a temperature of 54°C, the current is 36A / dm 2 Electrolysis was carried out for 50 seconds at a current density of 1.50 μm to obtain a first copper foil with a thickness of 18 μm.
[0048] After the first copper layer is prepared, sulfuric acid and Cu2O3 at a concentration of 80 g / L are used on its surface. 2+ The surface roughness was adjusted by using H2SO4·5H2O electroplating solution with an ion concentration of 30g / L, and ellipsoidal copper particles were generated on the surface. The electroplating temperature was 40℃ and the current density was 25A / dm 2 , the electrolysis time is 7s.
[0049] After the roughened surface is prepared, sulfuric acid is used as a treatment liquid to spray and soak both sides of the copper foil for 20 seconds to remove surface impurities or oxide films. The treatment liquid is sulfuric acid with a concentration of 85g / L and a treatment liquid temperature of 40°C.
[0050] After removing impurities or oxide film on the surface of copper foil, the copper foil is brought into the isolation coating electrolyte for isolation coating preparation. The concentration of gritty anhydride in the adhesion layer metal electrolyte is 0.5g / L, the concentration of potassium pyrophosphate is 700mg / L, and the electrolyte temperature is 45°C. After 12s of electroplating, the surface metal liquid is removed by soaking and rinsing tank, and brought into the organic attachment liquid for physical adsorption. The organic attachment liquid is a benzotriazole aqueous solution with a concentration of 3g / L, the attachment liquid temperature is 35°C, and the immersion attachment time is 20s. Then, the isolation coating is obtained after being blown and dried in a blast oven at 150°C.
[0051] After the isolation coating is air-dried, the copper foil is placed in a solution containing 110 g / L sulfuric acid and Cu 2+ The ion concentration of H2SO4·5H2O is 97g / L. In an electrolyte at a temperature of 54°C, the current is 20A / dm 2 Electrolysis was performed for 8 seconds at a current density of 1.500 μm to obtain a second copper foil layer with a thickness of 3.0 μm.
[0052] After the second copper foil layer is electroplated, sulfuric acid concentration is 90g / L, Cu 2+ Electroplating is performed in a copper sulfate solution with an ion concentration of 25 g / L. The copper foil is introduced into the solution, with the second copper foil layer facing the anode plate and the first copper foil layer away from the anode plate. 2 The copper foil was then electroplated at an average current density of 95 g / L and Cu 2+ Solidification electroplating was carried out in a copper sulfate solution with an ion concentration of 55g / L and an electroplating current density of 15A / dm 2 , electroplating time 15s.
[0053] After the roughening process, the copper foil is electrolyzed in an electrolyte with a sulfuric acid concentration of 75g / L, a cobalt concentration of 10g / L, a boric acid concentration of 30g / L, and a sodium citrate concentration of 10g / L at a temperature of 40°C and a current density of 12A / dm 2 , treatment electroplating time 10s; then at a concentration of 85g / , zinc concentration 18g / L, chloride ion concentration 15ppm, boric acid 30g / L, sodium citrate 15g / L, electrolysis temperature 45℃, current density 10A / dm 2 , the electroplating time is 10s. Finally, the electrolyte or water stains on the surface of the copper foil are removed by spraying water washing and oven drying.
[0054] The ratio of the vertical copper bump radius (a) to the horizontal copper bump radius (b) of the copper foil separation force adjustment layer in this embodiment is a / b=1.2. The separation force adjustment layer roughness Rz=1.1μm, the interface expansion area ratio Sdr=1.95%, and the peak vertex density Spd=13850 (1 / mm 2 ) The copper foil and the prepreg are pressed together to form a copper clad laminate, and the copper clad laminate is cut into test specimens with a specification of 100*15 mm and tested on a precision copper foil electronic stripping machine. The separation force between the two layers of the copper foil measured at a vertical tensile angle of 90° is an average of 7.5 gf / cm and a range of 3.9 gf / cm.
[0055] The copper clad board is prepared by high temperature pressing of the copper foil and the prepreg, and after peeling, a printed circuit board made of the multi-layer copper foil can be obtained through subsequent steps of coating with a photosensitive film, exposure, development, copper plating, film removal, etching, surface treatment and cutting.
[0056] Example 2
[0057] The difference between Example 2 and Example 1 is that (1) the surface roughness of the separation force adjustment layer is adjusted, the separation force adjustment layer roughness Rz = 1.7 μm, the interface expansion area ratio Sdr = 23.3%, the peak vertex density Spd = 26140 (1 / mm 2); (2) the ratio of the vertical copper bump radius (a) to the horizontal copper bump radius (b) of the separation force adjustment layer was adjusted to a / b = 0.7. The copper foil and the prepreg were pressed together to form a copper clad laminate, and the copper clad laminate was cut into test strips with a specification of 100*15mm and tested on a precision copper foil electronic stripping machine. The average separation force between the two layers of the copper foil was measured at a vertical tensile angle of 90° to be 34.7gf / cm, with a range of 2.6gf / cm.
[0058] Example 3
[0059] The difference between Example 3 and Example 1 is that (1) the surface roughness of the separation force adjustment layer is adjusted, the separation force adjustment layer roughness Rz = 2.3 μm, the interface expansion area ratio Sdr = 38.2%, the peak vertex density Spd = 28350 (1 / mm 2 )(2) The ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) of the separation force adjustment layer was adjusted to a / b = 0.5. The copper foil and the prepreg were pressed together to form a copper clad laminate, and the copper clad laminate was cut into test strips with a specification of 100*15mm and tested on a precision copper foil electronic stripping machine. The average separation force between the two layers of the copper foil was measured at a vertical tensile angle of 90°, and the range was 4.8gf / cm.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that (1) the separation force adjustment layer deposition step is not performed during the copper foil production process. The roughness of the peeling layer of the sample is separation force adjustment layer roughness Rz = 1.1 μm, interface expansion area ratio Sdr = 9.0%, peak vertex density Spd = 9880 (1 / mm 2 ) The copper foil and the prepreg are pressed together to form a copper clad laminate, and the copper clad laminate is cut into test specimens with a specification of 100*15mm and tested on a precision copper foil electronic stripping machine. The average separation force between the two layers of the copper foil measured at a vertical tensile angle of 90° is 18.3gf / cm, and the range difference is 32.5gf / cm.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for accurately separating multiple layers of copper foil, characterized in that: By analyzing the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b), the separation force can be accurately analyzed to achieve accurate separation of multiple layers of copper foil; When the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) is 0.8<a / b≤1.6, after the two layers of copper foil are pressed at a temperature above 210°C, the separation force of the two layers of copper foil is between 5≤F<20gf / cm; When the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) is 0.5<a / b≤0.8, after the two layers of copper foil are pressed at a temperature above 210°C, the separation force of the two layers of copper foil is between 20≤F<50gf / cm; When the ratio of the vertical copper nodule radius (a) to the horizontal copper nodule radius (b) is 0.3<a / b≤0.5, after the two layers of copper foil are pressed at a temperature above 210°C, the separation force of the two layers of copper foil is between 50≤F<80gf / cm.
2. A multi-layer separable copper foil, characterized in that: The method according to claim 1 is used for accurate separation.
3. The multi-layer separable copper foil according to claim 2, characterized in that: The cross-sectional structures of the copper foil are respectively a carrier copper layer, a separation force regulating layer, an isolation coating layer, an ultra-thin copper layer, and a surface treatment layer from bottom to top.
4. The multi-layer separable copper foil according to claim 3, characterized in that: The surface roughness Rz of the carrier copper layer in contact with the ultra-thin copper layer is between 0.5≤x<3.0μm, Sdr is between 1.5≤y<20.0%, and the peak density Spd is between 5000≤y<30000 (1 / mm 2 ) 5. The multi-layer separable copper foil according to claim 3, characterized in that: The isolation coating is selected from one of an electrodeposited non-copper metal, an organic coating, and a mixed coating of an electrodeposited non-copper metal and an organic coating.
6. The method for preparing a multi-layer separable copper foil according to any one of claims 3 to 5, characterized in that: Here are the steps: (1) Electrolytic equipment to prepare the first copper layer: The electrolyte is a copper sulfate solution containing 110 g / L sulfuric acid and Cu 2+ CuSO4·5H2O with an ion concentration of 97g / L; in an electrolyte with a temperature of 54°C and a current of 36A / dm 2 Electrolysis was performed for 50 seconds at a current density of 1.50 μm to obtain a first copper foil with a thickness of 18 μm. (2) Surface roughness treatment: After the first copper layer is prepared, sulfuric acid and Cu2O3 at a concentration of 80 g / L are used on its surface. 2+ The surface roughness was adjusted by using a CuSO4·5H2O electrodeposition solution with an ion concentration of 30 g / L, and ellipsoidal copper particles were generated on the surface; the electrodeposition temperature was 40°C and the current density was 25 A / dm 2 , electrolysis time is 7s; After the roughened surface is prepared, sulfuric acid is used as a treatment liquid to spray and soak both sides of the copper foil for 20 seconds to remove surface impurities or oxide film; the treatment liquid is sulfuric acid with a concentration of 85g / L and a treatment liquid temperature of 40°C; (3) Preparation of isolation coating After removing impurities or oxide film on the surface of the copper foil, the copper foil is brought into an isolation coating electrolyte to prepare the isolation coating; The concentration of gritty anhydride in the metal electrolyte of the adhesion layer is 0.5 g / L, the concentration of potassium pyrophosphate is 700 mg / L, and the electrolyte temperature is 45°C; after 12 seconds of electroplating, the surface metal liquid is removed by an immersion rinse tank, and brought into an organic adhesion liquid for physical adsorption, the organic adhesion liquid is an aqueous solution of benzotriazole with a concentration of 3 g / L, the adhesion liquid temperature is 35°C, and the immersion adhesion time is 20 seconds; and then the isolation coating is obtained after air drying in a 150°C environment in an air drying oven; (4) Preparation of ultra-thin copper layer After the first layer of isolation coating is air-dried, the copper foil is placed in a solution containing 110 g / L sulfuric acid and Cu 2+ CuSO4·5H2O with an ion concentration of 97g / L; in an electrolyte with a temperature of 54°C and a current of 20A / dm 2 The electrolysis was carried out for 8 seconds at a current density of , and an extremely thin copper layer with a thickness of 3.0 μm was obtained; (5) Roughening treatment The copper foil obtained in step (4) is introduced into a sulfuric acid solution having a concentration of 90 g / L and Cu 2+ In the copper sulfate solution electrolyte with an ion concentration of 25g / L, the second copper layer is opposite to the anode plate, and the first copper layer is far away from the anode plate. 2 The copper foil was electroplated at an average current density of 95 g / L and Cu 2+ The curing electroplating was carried out in a copper sulfate solution with an ion concentration of 55g / L and an electroplating current density of 15A / dm 2 , electroplating time 15s; (6) Surface treatment layer The structure obtained in step (5) is first electrolyzed in an electrolyte with a sulfuric acid concentration of 75 g / L, a cobalt concentration of 10 g / L, a boric acid concentration of 30 g / L, and a sodium citrate concentration of 10 g / L at a temperature of 40°C and a current density of 12 A / dm 2 , electroplating time 10s; then at sulfuric acid concentration 85g / L, zinc concentration 18g / L, chloride ion concentration 15ppm, boric acid 30g / L, sodium citrate 15g / L, electrolysis temperature 45℃, current density 10A / dm 2 , the electroplating time is 10s; finally, the electrolyte or water stains on the surface are removed by spraying water washing and oven drying.
7. A printed circuit board, characterized in that: The multi-layer separable copper foil is prepared from any one of claims 3 to 5.